Quality of life among patients with autoimmune hepatitis in remission: A comparative study. Issue 43 (23rd October 2020) - Takahashi, Atsushi; Abe, Masanori; Yasunaka, Tetsuya; Arinaga-Hino, Teruko; Abe, Kazumichi; Takaki, Akinobu; Torimura, Takuji; Zeniya, Mikio; Yoshizawea, Kaname; Kang, Jong-Hon; Suzuki, Yoshiyuki; Nakamoto, Nobuhiro; et al.
Abstract : Abstract: Health-related quality of life (HRQOL) is lower in individuals with autoimmune hepatitis (AIH) than in the general population. However, previous evaluations of HRQOL for AIH have included a broad range of disease activities. The aim of this study was to clarify HRQOL among patients with AIH in remission. We assessed HRQOL in patients with AIH in remission, patients with chronic hepatitis C (CHC) with eradicated hepatitis C virus (HCV) and patients with primary biliary cholangitis (PBC) using the Japanese version of the Chronic Liver Disease Questionnaire (CLDQ). Participants comprised 62 patients with AIH in remission, 39 patients with CHC with eradicated HCV and 66 patients with PBC. Median ages of patients were 63, 69, and 64 years, respectively. Overall score (5.6 vs 5.9, P = .02) and fatigue (5.2 vs 5.6, P = .01) and worry (5.6 vs 6.0, P = .01) domain scores of the CLDQ were significantly lower in patients with AIH in remission than in CHC with eradicated HCV, and similar to scores except for the systemic symptoms domain in patients with PBC. Disease duration was associated with lower scores on systemic symptoms and activity domains of the CLDQ in patients with AIH in remission. Patients with AIH in remission show impaired HRQOL associated with disease duration. Abstract : Supplemental Digital Content is available in the text